Intellectual Property Intensity Analysis of Economy Industries - Irina Ilina; Andrey Klypin; Sergey Vyunov; Alexey Vasyukov; Roman Tikhonov (Communications of International Proceedings, 2020)
The article describes a methodology for identifying priority areas of scientific and technological development of national economy industries. The analysis of patent activity in the article is based on such indicators as industry IP-capital intensity, industry IP-balance and industry IP-labor capacity. The choice of indicators is determined by the relationship between GDP, the average number of researchers and the level of application of intellectual property results. According to the comparison of the proposed coefficients with the average value for the national economy groups of high, medium and low intellectual property intensity industries are defined. To support industries, identified in the article as low intellectual property intensity industries, the authors propose amendments to the state policy tools in the field of intellectual property, earlier defined by the national project «Science» in the Russian Federation.
Keywords: Intellectual Property; Scientific Development; Patent; Industrial Analysis; IP Intensity